Africa Day: Effectiveness of integrated Agriculture, health livelihood and nutrition interventions to improve maternal and child nutrition and health in rural Uganda: A birth cohort study. - Kinyate, Florence (Tufts University. Tisch Library., 2017)
This poster presentation provides an overview of the birth cohort studty the Nutrition Innovation Lab conducted in Uganda, providing some of the prelimiary results on topics such as maternal wasting, anemia, water contamination levels, food security, and diet diverstiy scores.; Keywords: Makerere University, IFPRI, Tufts University.